ANALISIS EFISIENSI ENERGI PADA BOILER INDUSTRI TIPE FIRE-TUBE KAPASITAS 2TON/JAM DENGAN BAHAN BAKAR COMPRESSED NATURAL GAS (CNG) DI PT.X - Achmad Husen (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT Boiler is a high pressure vessel or tank that functions to produce hot steam. Problems that often occur in the field on boiler machines are not efficient well when the work system or operating process in the field, especially when the process is under operating conditions on a fire tube boiler engine always experiences heat loss in the steam or steam system and the fuel system which affects the efficiency of the engine. fire tube boilers are not optimal for steam output. Therefore, with these conditions, it is necessary to calculate the efficiency of a good fire tube type boiler engine in order to meet the appropriate efficiency value standards in the operating process in the field. The method used in this study is the calculation of efficiency carried out by two methods, namely the direct method and the indirect method. Based on the results of efficiency calculations using the direct method, the efficiency value is 81.04%, while the results of calculations using the indirect method are 85.65%. The results of the calculation of efficiency values ​​that have been carried out from two methods, namely the direct and indirect methods meet the standard efficiency value of the boiler engine ≥ 80 %. Keywords: Fire Tube Boiler, Efficiency, Heat Loss, Direct and Indirect Method